Analisis Desain Perkerasan Jalan Kaku dengan Menggunakan Metode Bina Marga (MDPJ 2024 dan MKJI 1997): Studi Kasus: Jalan Ruas Sp. Brongkos – Ngembul. Kec Kesamben, Jawa Timur - Ghany Setio Lusty; Hendrig Sudradjat; Hazairin Nikmatul L (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
This study analyzes the design of the width and rigid pavement of the road on Sp. Brongkos – Ngembul, Kesamben District, Blitar Regency, along 4.5 km with an existing road width of 5 meters, rumija 16.8 meters. The surrounding area includes forestry, residential, plantation, industrial, and Jolosutro Beach tourist access, with increased traffic density during the holiday season and industrial operations. The method used is descriptive quantitative based on LHR and CBR data. The calculation of lane width using MKJI 1997 (Indonesian Road Capacity Manual) shows the need for widening of 3 meters per lane and 2 meters of shoulder. The rigid pavement design using the MDPJ 2024 method (Road Pavement Design Manual) consists of a layer of coarse-grained soil embankment, class A aggregate, lean concrete, and structural concrete with a thickness of 200 mm, 200 mm, 150 mm, and 200 mm, respectively. With the JPCP design, for the tie bar connection reinforcement with a diameter of 16 mm, a length of 700 mm, a distance of 70 cm, and a dowel with a diameter of 28 mm, a length of 45 cm, and a distance of 30 cm.